Message from Director (Trinity Journal of Management, IT & Media (TJMITM), 2022)
The need of an hour is to enhance and uplift our skills and make ourselves suitable for the continuously and rapidly evolving efficient business practices in different spheres. The conference is specially to put a bright light on "Resilience and Reinvention: A Path for Change in Management, IT, Media and Law". The dynamic competitive landscape, pace of technology change, shifting customer expectations and demands, adapting with the needs of workforce are the major drivers of change in the extensive range of various sectors. It is salient for all the businesses to make decisions strategically by being more adaptable and structured with effective administration and implementation, with a focus on resilience and re-invention. The conference proceedings contain research papers contributed by academicians, students, research scholars and experts from different fields, giving a holistic perspective on the given theme. I believe that such conferences shall prove to be a great force enlightening people towards the importance of transformation of jobs, skills according to the challenging situation in the coming future as well in the society. I offer my gratitude to all those who are a part of this Conference for their valuable contributions. I sincerely appreciate the efforts and contributions of all the participants and authors to contribute for TIPSCON-2022.